The role of illicit drugs in developing medication-related osteonecrosis (MRONJ): a systematic review. Issue 4 (May 2021) - Sacco, R.; Ball, R.; Barry, E.; Akintola, O.
Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a challenging condition to treat. It has primarily been associated with anti-resorptive and anti-angiogenic drugs, which are increasingly being used to prevent adverse skeletally-related complications in patients with cancer and bone pathologies. Although these medications have been proven to cause osteonecrosis of the jaws (ONJ) there are also a number of other drugs that could potentially cause this condition. The aim of this systematic review is to ascertain whether there is an associated risk of osteonecrosis of the jaw (ONJ) in recreational drug users (RDU). Three authors independently searched PubMed, MEDLINE, EMBASE, CINAHL and the Cochrane Central Register of Controlled Trials for published reports of osteonecrosis of the jaw (ONJ) in recreational drug users (RDU) or illicit drug users (IDU) who had no history of treatment with anti-angiogenic or anti-resorptive agents. Only 30 studies were eligible for analysis, and all were independently assessed for risk of bias. There was a total of 101 patients with ONJ attributed solely to illicit drug consumption. The most common site of ONJ was the maxilla (n = 54). The most common illicit drug related to ONJ was desmorphine, known as 'Krokodil', this was followed by cocaine, methamphetamine, anabolic steroids, and hydrocodone/acetaminophen. In 52 of the cases, the ONJ resolved following treatment, however, eight showed a recurrence. Although all the studies were judged to be at a high risk of bias, the limited data suggest that some patients are at risk of developing ONJ as a result of illicit drug usage. Studies of higher quality are needed to establish the relative risk of ONJ in this patient group.